Numerical Analysis of the Crashworthiness Performance of Multicell Tubes Under Oblique Loads - Estrada Barbosa, Quirino (2024)
When a car crash occurs, the probability that the collision will be oblique and not entirely frontal is high. In this way, the current article evaluates by a finite element analysis, the crashworthiness performance of multicell structures subjected to oblique loads. In this sense, five multicell structures manufactured with 6063-T5 aluminum alloy were designed and evaluated by an oblique compression test. During the analysis, special emphasis was placed on determining the effect of the cross-section and the angle of incidence of the load (θ) on the energy absorption of the structures. For this purpose, values of θ equal to 0°,5°,10° and 15° were analyzed. To guarantee a correct comparison between tubes, all the structures had the same mass equal to 0.80 kg. Then, adjustments to the thickness were realized. In all cases, the most important indicators of impact resistance such as energy absorption (Ea), crushing force efficiency (CFE), and mean force (Pm) were calculated. According to the results, the angle of incidence of the load defined the plastic deformation mode of the structure. In this sense, a 47.75% decrease in the Pmax and Pm was observed as the angle θ increased. Moreover, at the end of the study, the MC-02 profile presented the best CFE with an average value of 0.74 at different loading angles. Thus, this structure could be considered as a baseline among engineers and designers for the design of structures subjected to bending loads.